2004
DOI: 10.1042/bj20040544
|View full text |Cite
|
Sign up to set email alerts
|

Functions of NF-κB1 and NF-κB2 in immune cell biology

Abstract: Two members of the NF-kappaB (nuclear factor kappaB)/Rel transcription factor family, NF-kappaB1 and NF-kappaB2, are produced as precursor proteins, NF-kappaB1 p105 and NF-kappaB2 p100 respectively. These are proteolytically processed by the proteasome to produce the mature transcription factors NF-kappaB1 p50 and NF-kappaB2 p52. p105 and p100 are known to function additionally as IkappaBs (inhibitors of NF-kappaB), which retain associated NF-kappaB subunits in the cytoplasm of unstimulated cells. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
522
0
24

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(556 citation statements)
references
References 191 publications
(338 reference statements)
10
522
0
24
Order By: Relevance
“…Previous reports demonstrated that NF-kB is an important transcriptional regulator of Bcl-2 and Bcl-XL (Mori et al, 2001;Sevilla et al, 2001;Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004). NF-kB is a family of transcription factors composed of homo-and heterodimers of Rel family polypeptides: p50, p52, RelA (p65), RelB and c-Rel (Rel) (Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports demonstrated that NF-kB is an important transcriptional regulator of Bcl-2 and Bcl-XL (Mori et al, 2001;Sevilla et al, 2001;Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004). NF-kB is a family of transcription factors composed of homo-and heterodimers of Rel family polypeptides: p50, p52, RelA (p65), RelB and c-Rel (Rel) (Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB is a family of transcription factors composed of homo-and heterodimers of Rel family polypeptides: p50, p52, RelA (p65), RelB and c-Rel (Rel) (Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004). In non-simulated cells, NF-kB is inactivated by binding to IkB in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate study by Enzler et al showed that all major components of the non-classical NF-κB pathway are crucial for BAFF-mediated survival [26•]. Further, while knockout mice for the components of each pathway differ slightly, all are essentially similar to BAFF −/− or BAFFr −/− mice [20,[34][35][36]. Thus, it seems likely that the BCR and BAFFr are coupled through these two signaling systems, either via simultaneous activation targeting separate promoters of survival, or through direct cross-talk.…”
Section: Baff/baffr Signaling Integrates Primary B Cell Selection Andmentioning
confidence: 99%
“…This protein complex is also involved in activation of effector cells through toll‐like receptors (TLRs) in response to GI micro‐organisms. Dysregulation of the activation of NF‐κB can lead to overproduction of pro‐inflammatory cytokines and cell transformation, triggering the development of cancers in humans 25, 26, 27…”
Section: Introductionmentioning
confidence: 99%